"Cocoa Pods". Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
A picture of a large pile of cocoa pods.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cacao--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago